Optic flow influences perceived exertion and distance estimation but not running pace - Parry, D.; Micklewright, D. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to examine the effect of variations in optic flow on perceived and actual running pace and RPE.